A retrospective cross sectional study on neurological profile of children with congenital heart disease - Banerjee, Asish; Mitra, Meenakshi (International Journal of Research in Medical Sciences, 2019)
Background: Children with Congenital Heart Disease have associated structural neurological abnormalities and those surviving infancy are even subjected to various environmental factors which might contribute to neurological abnormalities. Hence the objective is to study the neurological abnormalities of children with Congenital Heart Disease. Methods: A retrospective cross-sectional observation study was conducted over the period of 3 years (June 2016-May 2019). Data were collected from medical records department of 121 children of 2-12 years of age diagnosed with congenital heart disease. Neurological examination findings and neuro imaging and EEG findings where relevant were noted. To assess the association of adverse neurological outcome and congenital heart disease, data analysis was performed using Fisher’s exact test. Results: 38% children of 2-12 years of age with congenital heart disease had adverse neurological profile. Neurological abnormalities were significantly associated with cyanotic heart disease (p value 0.0001). Statistically significant association were found between congenital cyanotic heart disease and seizure (p value=0.04), hemi paresis (p value=0.039), brain abscess (p value=0.012) and coma (p=0.01). Conclusions: Congenital cyanotic heart disease has significant associations with neurological abnormalities in children. These results demand attention for the neurological health of the largely uncorrected cardiac disease in Indian children